THE PECKING ORDER BEHAVIOR OF CAPITAL STRUCTURE: EVIDENCE FROM PALESTINIAN CORPORATIONS - Mohammad Nasser Jaradat (My University, 2022)
Abstract Research Background: Financing policies have a significant impact on the profitability and performance of companies. Several theories, including the pecking order theory, have talked about capital structure. This study sought to find out the extent of the applicability of the pecking order theory on the financing policies in Palestinian companies. Aim of the Study : This study aimed to find out the extent to which the pecking order theory applies to financing policies in Palestinian companies, whether in terms governing them, and identifying the determinants of leverage . In addition, it is of interest to understand what the direction of the relationship is between these variables and this leverage. Methodology: The researcher used the quantitative research method. Heused a data panel for a Palestinian company from 2006-2019. The multiple linear regression method was used to analyze data, test the hypothesis, and identify the relationships between the variables. Results of the Study: After data analysis, it was found that the financial deficit was the actual ruler of the debt ratio in the Palestinian companies, and the direction of relationship was positive. There was aslo a positive relationship between deficit and net debt issued. However , there was a negative relationship between financing deficit and retained earnings. Furthermore, there was a negative relationship between net debt issued and cash dividends, cash flow after interest and tax, but a positive relationship between net investment and change in working capital. Another promising finding was that the conventional variables tangibility and market-to-book ratio and size had a positive relationship with leverage but a negative relationship with profitability and leverage. Conclusions: The pecking order theory is the ruler of the financing policies in the Palestinian companies, and the Palestinian companies depend on retained earnings and debt to finance their investments. Keywords: Pecking order theory; financing deficit; leverage; capital structure.